Engineering and characterization of probiotics to tackle fructose-induced metabolic syndrome - Au-Yeung, Benjamin Shang Yong (Nanyang Technological University, 2020)
The twin epidemics of obesity and diabetes are the primary metabolic disorders fuelled by processed food availability and modern lifestyles. No current medical interventions and treatments have been successful in reversing their rising trends. Thus far, multiple causal factors have been identified with fructose being singled out by many as the major driver for this upward trajectory. Apart from the liver, most body cells lack sufficient GLUT5 transporters for fructose uptake which results in the bulk of fructose metabolism being concentrated in the liver; the immense stress placed on that single organ would lead to hepatic de novo lipogenesis and hepatic insulin resistance. Besides excess fructose, Saturated Fatty Acids (SFA) are also macronutrients to watch out for since they raise cholesterol levels and increase risk of cardiovascular diseases; both fructose and SFA are detrimental macronutrients that health authorities/bodies recommend the population to consume less of. With the advancement in synthetic biology, engineering probiotics could offer new means to tackle these metabolic diseases. A potential solution could be to have fructophilic probiotic (e.g. Lactobacillus kunkeei) metabolize the excess dietary fructose in the gut, and have an engineered probiotic SFA genetic biosensor to detect high dietary SFA content for appetite regulation. However, there are apparent gaps towards achieving this goal: (1) current mice models for fructose-induced metabolic syndrome give a myriad of findings that do not agree with each other; (2) there is a lack of characterization studies measuring fructose consumption amounts for L. kunkeei; (3) current fatty acid biosensors detect fatty acids in general but are not specific enough to sense and discriminate SFA, and the biosensors are not developed using probiotics as the host. This thesis presents a number of studies to overcome abovementioned gaps. First, the thesis presents a study on a mice model which shows fructose-induced hepatic steatosis with low bodyweights, very similar to the Non-Alcoholic Fatty Liver Disease (NAFLD) phenotype in non-obese populations within society. Findings from the mice study imply that liver fibrosis along with increased hepatic triglyceride and lipid storage are the very possible outcomes from excessive consumption of added fructose in the diet. Second, this thesis also provides a better understanding of L. kunkeei, its fructophilic nature and basic genetic tools to engineer it. The results show that L. kunkeei outperforms commonly used probiotics, Lactobacillus rhamnosus and Escherichia coli Nissle, in fructose metabolism/uptake rate. Last but not least, a genetic fatty acid biosensor was developed in E. coli Nissle to be able to detect SFA with up to ~8-fold change in readings. This biosensor could eventually work alongside with the probiotic L. kunkeei as a co-culture treatment; both probiotics address metabolic syndrome via restricting calorie consumption of detrimental macronutrients. Ultimately, the findings from this thesis form a foundation to enable future development of probiotic treatment which could improve overall state of health and significantly reduce the risk of obesity and type 2 diabetes mellitus.